Assessment Of Mania With Self Rating Scale - Shakya, R.; Khandelwal, S.K.; Sagar, R. (Journal of Psychiatrists’ Association of Nepal, 2017)
Introduction: Patients with mania are generally considered unreliable informants about their illness and most of the mania rating scales are clinician administered. There are few self-rating scales in mania and the utility of which is immense. Objective: The study was aimed to compare the co-relation between the self-rating scales and clinician rating scales in mania. Method: Forty-two patients with mania in the tertiary care center of North Indian setting were applied with Clinician Administered Rating Scale for Mania,Altman Self-Rating Mania scale, Hamilton Rating Scale for Depression and Clinical Global Impression Scale at base line and consecutive four weeks. The scores were analyzed for correlation. Result: The Pearson’s correlation coefficient rho between self rated vs. clinician in the first week scores was 0.368 with p value of <0.05. On the subsequent weeks the rho value progressively increased and became highly significant (p<0.01). Conclusion: Self-reporting by mania is reliable in looking at the symptoms. Self rating scale is not very reliable when the patient is very severely ill, at least to predict the severity /improvement, but, reliable when the patient improves from very severe illness to moderate or milder degree. The scale can be utilized as an augmentation to the clinical interview.